2018
DOI: 10.1111/auar.12227
|View full text |Cite
|
Sign up to set email alerts
|

If You Can Measure It, You Can Manage It: A Case of Intellectual Capital

Abstract: Despite the great importance attributed to intellectual capital (IC) in the past two decades or so, its measurement and management have remained elusive, mainly because of inappropriate prior models of IC measurement. The purpose of this study is, therefore, to make adjustments to an existing model, the Value Added Intellectual Coefficient (VAIC), and to present an adjusted‐VAIC model to measure IC. We tested our new model on data from 10 emerging and developed world markets and obtained more consistent result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
143
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(170 citation statements)
references
References 56 publications
(88 reference statements)
18
143
3
6
Order By: Relevance
“…Analyzing the data of financial institutions in Pakistan, Haris et al [40] documented that HC exhibits a positive impact on bank profitability while SC has a negative impact. Nadeem et al [41], using an adjusted-VAIC TM model, found that IC and its components (human, innovation and physical capitals) positively influence firm performance. Xu and Li [42] determined the impact of IC on firm performance in the context of China's manufacturing small and medium-sized enterprises (SMEs).…”
Section: Ic and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the data of financial institutions in Pakistan, Haris et al [40] documented that HC exhibits a positive impact on bank profitability while SC has a negative impact. Nadeem et al [41], using an adjusted-VAIC TM model, found that IC and its components (human, innovation and physical capitals) positively influence firm performance. Xu and Li [42] determined the impact of IC on firm performance in the context of China's manufacturing small and medium-sized enterprises (SMEs).…”
Section: Ic and Firm Performancementioning
confidence: 99%
“…For the dependent variable, firm performance is measured with return on assets (ROA), consistent with previous literature [1,5,6,22,23,30,41,42,79]. ROA measures how efficiently a firm utilizes and manages its assets to produce profits during a certain period.…”
Section: Variable Measurementmentioning
confidence: 99%
“…Wang et al [12] argued that IC plays an important role in achieving high levels of bank efficiency in East Asia. Nadeem et al [68] presented an adjusted-VAIC model to test the impact of IC and its components (human, innovation and physical assets) on firm performance in 10 emerging and developed economies. The results showed that the impact of IC varies greatly in different countries.…”
Section: Ic and Firm Performancementioning
confidence: 99%
“…Accounting practices do not seem to offer a solution; it has been a common remark over the years that the statements provided by financial accounting do not give a clear picture of many of the “hidden” realities that comprise a company and its business. In fact, even though it is generally accepted that investments in intangibles are important sources of future performance, restrictive accounting asset recognition rules mean that most intangible assets cannot be included in the balance sheet (Nadeem, Dumay, & Massaro, ), especially if they are internally developed. As stated by Dumay and Rooney (), IC accounting research and practice is a problematic theme.…”
Section: Introductionmentioning
confidence: 99%